Animal Models of Human Viral Diseases - Ruiz, Sara I. (Animal Models for the Study of Human Disease, 2017)
As the threat of exposure to emerging and reemerging viruses within a naïve population increases, it is vital that the basic mechanisms of pathogenesis and immune response be thoroughly investigated. Recent outbreaks of Middle East respiratory syndrome corona virus, Ebola virus, Chikungunya virus, and Zika virus illustrate the emerging threats that are encountered. By utilizing animal models in this endeavor, the host response to viruses can be studied in a more complex and integrated context to identify novel drug targets, and assess the efficacy and safety of new products rapidly. This is especially true in the advent and implementation of the FDA animal rule. Although no one animal model is able to recapitulate all aspects of human disease, understanding the current limitations allows for a more targeted experimental design. Important facets to consider prior to an animal study are route of viral exposure, species of animal, biomarkers of disease, and a humane endpoint. This chapter covers the current animal models for medically important human viruses, and demonstrates where the gaps in knowledge exist.